Religion as Meaning-Making Resource in Understanding Suicidal Behavior in Ghana and Uganda - Knizek, Birthe Loa; Andoh-Arthur, Johnny; Osafo, Joseph; Mugisha, James; Kinyanda, Eugene; Akotia, Charity; Hjelmeland, Heidi (Frontiers in Psychology, 2021)
Suicidal behavior is condemned by religions and tradition and suicide attempts are criminalised by law in several African countries, including Ghana and Uganda. Suicide and suicide attempts may have severe consequences for both the entire family and the community. Religion is known to act as a protective coping force that helps people to make meaning and find comfort when dealing with stressful life events or situations like suicide. In this article we focus on the cultural interpretations of the dominating religion in Ghana and Uganda, Christianity, and whether these affect attitudes towards suicidal behavior, meaning-making, and coping possibilities for people who have attempted suicide or are bereaved by suicide. This article is based on data material from previous studies on the mentioned topics by the authors.